Chongqing 2035 : A Regional Strategy to Increase Connectivity and Economic Integration - World Bank (World Bank, Washington, DC, 2019)
Cities can increase economic growth and participate in global economic flows by acting as hubs or gateways to regional corridors, that are supported by three dimensions of connectivity: physical (infrastructure) connectivity, digital connectivity, and economic integration. Integrating these dimensions increases economic output and generates more high-quality jobs. Connectivity integration also helps a city accumulate knowledge and has positive spillover effects for the broader economy. Chongqing stands out for its well-developed infrastructure and digital connectivity, but it has yet to leverage these assets to promote regional economic integration. This report recommends: leverage existing transport infrastructure and supplement it with better integration between land, air, and water transport to build a major logistics hub; strengthen cooperation with Chengdu, Sichuan, and other regional partners to promote regional economic integration; and improve digital infrastructure with faster internet connection speeds and promote the wider adoption of digitization of services.